A hydrate salt-promoted reductive coupling reaction of nitrodienes with unactivated alkenes. Issue 8 (6th February 2019) - Zhang, Mengmeng; Yang, Liming; Tian, Chao; Zhou, Meng; An, Guanghui; Li, Guangming
Abstract : Na2 HPO4 ·7H2 O has been disclosed as an effective promoter for mild and efficient reductive coupling of nitrodienes with alkenes in an open flask manner. Abstract : Transition metal-catalyzed reductive coupling has emerged as a powerful method for the construction of C–C bonds. Herein, a crystalline hydrate, Na2 HPO4 ·7H2 O, has been disclosed as an effective promoter for the reductive coupling of nitrodienes with unactivated alkenes to afford diverse dienes with various functionalities in an open-flask manner. The mechanism study has revealed that Na2 HPO4 ·7H2 O accelerates the in situ generation of active silane PhSi(OEt)H2 and prevents the deactivation of catalyst. The approach can increase the efficiency of previous reductive coupling reactions as well.